Sexual Risk Behaviour and its Associated Factors Among University Students in Malaysia - Fadzilah Mohamad; Khairatul Nainey Kamaruddin; Nur Amirah Shibraumalisi; Sharifah Najwa Syed Mohamad; Syifa Mohd Azlan; Rahima Dahlan; Irmi Zarina Ismail; Hayati Kadir Shahar; Nurainul Hana Shamsuddin (Springer Nature, 2026)
Tier 2